Ask questions and get helpful answers.

Use the Substitution method to solve the system of equations.

y - 2x = -5
3y - x = 5

Solve one of the equations for x or y.

Let's solve the first one for y:
y - 2x = -5
y = 2x - 5

Now let's substitute 2x - 5 for y in the second equation to solve for x:
3(2x - 5) - x = 5
6x - 15 - x = 5
5x - 15 = 5
5x = 20
x = 4

Substitute 4 for x in either equation to solve for y. Let's choose the first one.
y - 2(4) = -5
y - 8 = -5
y = 3

There you have it! Check the solution with both equations to make sure we have the right solutions. It always helps to check your work!

I hope this will help.

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
5 answers
  1. Yes

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  2. Solve :4g-6h-5g-3g+10h+6g

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  3. 2m+n=0
    M+2n=3

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  4. mathway.com is a big help

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  5. How will I solve the substitutions of simultaneous equation of ×+y=4
    2×-y=5

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.